Guiding principles and practices of peace education followed in secondary schools of Mizoram - Lokanath Mishra; Tushar Gupta; Abha Shree (Institute of Advanced Engineering and Science, 2020)
The significance of peace education is universally recognized for a safe and prospering future for the world at school level as peace education aims at equipping the future citizens with necessary knowledge, attitude and skills so that they would acknowledge and respect all kinds of diversity and understand human dignity. This paper is based on an empirical research aiming how far guiding principles and practices of peace education followed in secondary schools of Mizoram. The concept of peace education, guiding principles of peace education and practices on peace-related activities being followed in the secondary schools of Mizoram were explored. The study revealed that peace education was not being taught as a separate subject. Peace education component was infused in the existing curriculum and also was being taught through co-curricular and extra-curricular activities. Besides, teachers must reflect in their behavior all the guiding principles of peace. They should encourage the students for critical thinking, reasoning, develop awareness on societal problems and issues, broaden their outlook, concentrate on studies, and to be associated with various activities. In Mizoram, students’ unions and church organizations used to play a prominent role in shaping and moulding the character of the people starting from the early stage of life which ultimately benefits the society and the nation. However, in the context of rapid change in social structure and modernization process, there is need for inculcating the values of peace for which schools have to play important role.